Filsafat Progresivisme Perkembangan Peserta Didik - Ibrahim, Ruslan (Al-Riwayah : Jurnal Kependidikan, 2018)
This article explains the philosophical view of progressivism about learners. Progressive philosophy sees that education is not just transferring knowledge to learners, but training their abilities and skills by providing the right stimulus. In the field of education, this philosophy was pioneered by the educational leader, John Dewey, with the main jargon of education as an instrument of social reconstruction. Progressive philosophy has the principle that learners should be educated to be human beings who can understand life in the future. For that, learners should be allowed to be free, active, creativity, and dynamic in accordance with the context of life.